Nature Conservation in Islam: an Analysis on M. Quraish Shihab’s Qur’anic Interpretation - Rani Tania Riatno (AJIS: Academic Journal of Islamic Studies, 2017)
Nowadays, environmental problems have become hot and interesting issues to discuss. Natural damages which occur in almost all parts of the world have attracted serious attention among experts and nature lovers as well as motivated them to work out to save the environment from demages. Besides theoretical concept of how to reduce nature damages, many efforts have been done in order to preserve the nature. Some of these exertions result in success, but some of them get failed. Consequently, it occurs to some people to seek for another solution or outlook, namely from the perspective of religion. It is to say that among moslem scholars there is a strong belief that Islam has provided specific guidelines pertaining to the conservation of universe. Some of them can be traced in the divine verses throughout the book of al-Qur’an. In line with this notion, the writer is interested in exploring the concept of Islam on nature preservation in the field of tafsir (Qur’anic exegesis). The present article will examine nature conservatory understanding of an outstanding scholar in Indonesia, M. Quraish shihab, whose quite extensive books on tafsir are entitled “Tafsir al-Misbah”. Shihab’s thought deserves our attention because he has paid much interest in his books of tafsir on the issues of nature and its preservation.